Addition of pathology and biomarker information significantly improves the performance of the Manchester scoring system for BRCA1 and BRCA2 testing. Issue 12 (18th June 2009) - Evans, D G R; Lalloo, F; Cramer, A; Jones, E A; Knox, F; Amir, E; Howell, A
Abstract : Background: Selection for genetic testing of BRCA1/BRCA2 is an important area of healthcare. Although testing costs for mutational analysis are falling, costs in North America remain in excess of US3000 (UK price can be £690). Guidelines in most countries use a 10–20% threshold of detecting a mutation in BRCA1 /2 combined within a family before mutational analysis is considered. A number of computer-based models have been developed. However, use of these models can be time consuming and difficult. The Manchester scoring system was developed in 2003 to simplify the selection process without losing accuracy. Methods: In order to increase accuracy of prediction, breast pathology of the index case was incorporated into the Manchester scoring system based on 2156 samples from unrelated non-Jewish patients fully tested for BRCA1/2, and the scores were adapted accordingly. Results/Discussion: Data from breast pathology allowed adjustment of BRCA1 and combined BRCA1/2 scores alone. There was a lack of pathological homogeneity for BRCA2, therefore specific pathological correlates could not be identified. Upward adjustments in BRCA1 mutation prediction scores were made for grade 3 ductal cancers, oestrogen receptor (ER) and triple-negative tumours. Downward adjustments in the score were made for grade 1 tumours, lobular cancer, ductal carcinoma in situ and ER/HER2 positivity. Application of the updated scoring system led to four and nine more mutations in BRCA1 being identified at the 10% and 20% threshold, respectively. Furthermore, 65 and 58 fewer cases met the 10% and 20% threshold, respectively, for testing. Moreover, the adjusted score significantly improved the trade-off between sensitivity and specificity for BRCA1/2 prediction.